First report of organochlorine pesticides (OCPs) in coral tissues and the surrounding air-seawater system from the South China Sea: Distribution, source, and environmental fate. (January 2022) - Kang, Yaru; Zhang, Ruijie; Yu, Kefu; Han, Minwei; Wang, Yinghui; Huang, Xueyong; Wang, Ruixuan; Liu, Fang
Abstract: The levels, fate, and potential sources of 22 organochlorine pesticides (OCPs) in coral tissues and the surrounding air-seawater system from the South China Sea (SCS) were elucidated for the first time. ∑22 OCPs (total concentration of 22 OCPs) (16.1–223 pg L −1 ) was relatively higher in coastal seawater than in offshore seawater, which may be the widespread influence of coastal pollution inputs under the western boundary current. The atmospheric ∑22 OCPs were predominantly distributed in the gas phase (48.0–2264 pg m −3 ) and were mainly influenced by continental air mass origins. The air-seawater exchange of selected OCPs showed that OCPs tended to migrate from the atmosphere to seawater. The distribution of ∑22 OCPs in coral tissues (0.02–52.2 ng g −1 dw) was significantly correlated with that in air samples, suggesting that OCPs may have a migration pattern of atmosphere-ocean corals in the SCS. Corals exhibited higher bioaccumulation ability (Log BAFs : 2.42–7.41) for OCPs. Source analysis showed that the new application of technical Chlordanes (CHLs) was primarily responsible for the current levels of CHLs in the surrounding environment over the SCS, while historical residues were the primary sources of other OCPs. Graphical abstract: Image 1 Highlights: Pioneer OCPs study of coral tissues from the South China Sea (SCS). Corals presented a higher bioaccumulative ability to OCPs. Ocean currents and monsoons played essential roles in the OCPs' spatial distribution. Net atmospheric deposition of OCPs occurred in the coral reef regions (CRRs), SCS. OCPs may have a migration pattern of atmosphere-ocean-corals in the CRRs, SCS.